Dealers’ Market Orientation And Brand Equity: The Mediating Effect Of Relationship Marketing - Ghani, Noor Hasmini Hj Abd (2011)
The reliance of car manufacturers on their sales dealers in a very competitive market, which have created selling pressures justified the importance of investigating brand equity from the latter’s perspective. Generally, the Malaysian brands including the car brands have been perceived to have low brand equity. From literature, the importance of market orientation and relationship marketing cannot be ignored. Hence, the study attempts to investigate the role of market orientation and relationship marketing in forming the brand equity.